The Effects of Sampling A Natural Silty Clay - Lopes, Rui (My University, 1970)
The effects of sampling on the strength and preconsolidation load of a normally consolidated natural silty clay have been studied by means of laboratory simulations of "perfect" samples, "ground" samples, "tube" samples and "bottom of failed borehole" samples.
Keywords: silty; natural clay; laboratory simulation